Effect of injection hatching eggs with Newcastle disease vaccine and different doses of vitamin E on some productive traits and immune response of broilers - Abdulwahid, Mushtaq T. (The Iraqi Journal of Veterinary Medicine, 2015)
This study aimed to investigate the effects of injection hatching eggs with different doses of vitamin E on productive traits, some physiological and immune response to Newcastle disease vaccine. Two hundred fertile eggs of broiler breeder Ross (308) strain were incubated in automatic incubator machine after divided into four treatments (50 eggs per treatment) with two replicates. First treatment was injected 0.1ml/egg of phosphate buffer sterile into amniotic fluid at day 18th of incubation which it was considered as control group, second treatment was injected with 0.1ml/egg of inactivated Newcastle disease vaccine, third treatment was injected with 0.1ml/egg of inactivated Newcastle disease vaccine and 0.1 ml/egg of vitamin E, fourth treatment was injected with 0.1ml/egg of inactivated Newcastle disease vaccine and 0.15 ml/egg of vitamin E. All injected eggs were carried back into incubator for complete hatching process. Hatched chicks were transferred to the hall in farm of the Veterinary Medicine College/University of Baghdad; therefore, the chicks were distributed into four treatments with two replicates depending on the previously treated groups until fifth week of age. The results revealed that the treated groups with vitamin E were significantly (P≤0.05) increased in hatchability percentage, body weight, weight gain, as well as significant reduce in feed intake and improvement in feed conversion ratio as compared with second group and control, the results of third group showed significantly increased (P≤0.05) in antibody titers against Newcastle disease virus at aged (21 and 35) day as compared with the other treated groups and control.